2022
DOI: 10.21741/9781644901755-27
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Polymer Materials in the Composition of Asphalt Concrete

Abstract: Abstract. The research presented in the article shows the possibility of using some polymer materials in the composition of asphalt concrete. The analysis of scientific works in the field of asphalt concrete design shows the efficiency of using plastic waste to obtain asphalt concrete with specified physical, mechanical and operational properties. This technology allows not only to reduce the amount of accumulated plastic waste, but also to improve the condition of highways by increasing the strength of asphal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
1
Order By: Relevance
“…The introduction of new road-building materials with advanced physical and mechanical properties is the trend in contemporary civil engineering, which aims to increase the quality of road surfaces (Bieliatynskyi et al, 2022) and safety (St-Jacques et al, 2009). According to previous research work, the mixtures modified with recycled-plastic additives (Russo et al, 2022;Pugin et al, 2022), the addition of fiber from the fly ash of thermal power plants (Bieliatynskyi et al, 2022), the glass particle, showed higher stiffness and tenacity and as expected though, with specified physical, mechanical and operational properties in line with the literature. And asphalt with an added polymer material which is elastomeric can increase the durability of road pavements and the stability of the asphalt concrete mixture (Yanuar et al, 2021;Hadidane et al, 2015).…”
Section: Introductionsupporting
confidence: 82%
“…The introduction of new road-building materials with advanced physical and mechanical properties is the trend in contemporary civil engineering, which aims to increase the quality of road surfaces (Bieliatynskyi et al, 2022) and safety (St-Jacques et al, 2009). According to previous research work, the mixtures modified with recycled-plastic additives (Russo et al, 2022;Pugin et al, 2022), the addition of fiber from the fly ash of thermal power plants (Bieliatynskyi et al, 2022), the glass particle, showed higher stiffness and tenacity and as expected though, with specified physical, mechanical and operational properties in line with the literature. And asphalt with an added polymer material which is elastomeric can increase the durability of road pavements and the stability of the asphalt concrete mixture (Yanuar et al, 2021;Hadidane et al, 2015).…”
Section: Introductionsupporting
confidence: 82%
“…Использование материального ресурса отходов ПНД для получения вторичных гранул и других продуктов требует тщательной очистки отходов от различных загрязнений. Наличие нефтепродуктов в отходах в разы повышает расход моющих средств и формирует вторичный поток отходов в виде шламов [6][7][8][9][10][11]. Разработанные технологии использования материального ресурса отходов потребления из ПНД, без предварительной очистки от загрязнений, для получения высоких физико-механических характеристик, требуют количественной оценки содержания моторного масла в составе отходов ПНД [12].…”
Section: Introductionunclassified